Developing Basic English Module for Junior High School to Promote Students’ Cognitive Development - Agya, Ahmad Fadil; Meisuri, Meisuri (Raden Intan State Islamic University of Lampung, Indonesia, 2023)
A module is a supplementary tool for existing teaching materials, allowing students to engage in independent learning by exploring the concepts presented within the module. This approach can enhance students' competence and foster their enthusiasm for the subject. The research aims to ascertain the English material requirements of seventh-grade students at SMPN 4 Bandar Lampung and create a comprehensive English curriculum for this grade level at the abovementioned school. The ADDIE model was utilized to achieve the stated objectives. The need analysis was carried out before the creation of the material. Based on the expert judgment of the material, it has been determined that the average score (X) is 3.6. The score is classified as good due to its placement within the 3.5 < X < 3.75 interval. However, there are two aspects that experts believe require further improvement. These aspects include enhancing the accessibility of the module's materials for students to comprehend and ensuring that the illustrations align with the content presented in the module. To enhance the comprehensibility of the module's content for students, the expert recommended providing more explicit instructions for each step of the activities students must undertake.Regarding the illustrations provided per the module's content, experts have recommended incorporating additional illustrations to enhance the module's level of engagement. Based on the expert judgment and evaluation of the presentation, it has been determined that the average score (X) is 3.75. Based on the obtained score, the categorization can be deemed satisfactory, as the value of X falls within the interval of 3.5 < X < 3.75. The expert has recommended an enhancement of the references or supporting materials. The expert recommended incorporating additional references to enhance the comprehensiveness of the module. Based on the expert judgment of the material, it has been determined that the average score (X) is 3.75. Based on the obtained score, it can be classified as satisfactory, as the X value falls within the 3.5 < X < 3.75 range. The expert recommended one aspect for improvement, specifically regarding the alignment of language usage with the student's cognitive development stage. The expert posited that certain languages may present a level of complexity that surpasses students' cognitive abilities. Consequently, it is recommended that these languages be modified or adapted to better align with the student's learning capacities.